Meningitis Bakterial: Epidemiologi, Patofisiologi, dan Penatalaksanaan - Puji Widyastuti; Herdiana Nurul Utami; M. Fardi Anugrah; Rohadi (Lombok Medical Journal, 2023)
The brain is a complex, delicate neural organ protected by the skull, meninges and cerebrospinal fluid. This protection can be damaged by disease, such as bacterial meningitis. Its high morbidity and mortality results in the need for prompt diagnosis and treatment. This literature review uses a literature study method from various references and focuses on the incidence of bacterial meningitis with search engines, namely PubMed, ProQuest, and Google Scholar. Nineteen articles were found to be suitable for reference in this literature review. Bacterial meningitis is an inflammation of the meninges due to infection with the bacteria Streptococcus pneumoniae, Neisseria meningitidis, and Haemophilus influenzae type B. The incidence of bacterial meningitis worldwide reached 8.7 million cases with 379,000 deaths. In Indonesia, there were 78,018 cases with 4313 deaths. Symptoms of bacterial meningitis include fever, neck stiffness, and altered mental status with complications of focal neurologic deficits, hearing and cognitive impairment, seizures, and hydrocephalus. Treatment for bacterial meningitis includes antibiotics ceftriaxone, cephalosporin, penicillin, or ampicillin in combination with corticosteroids which should be given as soon as possible to minimize symptoms, complications, and mortality.